Realism And Islamic Education - Ine Ratu Fadliah (Universitas Muhammadiyah Enrekang, 2022)
This study describes realism and Islamic education. The method used in this study uses the library research, that literature or literature study can be interpreted as a series of activities related to library data collection methods, reading and recording and processing research materials. The results of this study indicate that education can be interpreted narrowly, and can also be interpreted broadly. Narrowly education can be interpreted: